ANALISIS KEARIFAN LOKAL TERHADAP PENGEMBANGAN EKONOMI LOKAL USAHA MIKRO KECIL DAN MENENGAH DI WISATA DANAU TOBA KECAMATAN GIRSANG SIPANGAN BOLON KABUPATEN SIMALUNGUN - Selamat Siregar; Tiur Rajagukguk (Fakultas Ekonomi Universitas Methodist Indonesia, 2018)
The purpose of this study was to determine the effect of local wisdom on local economic development in the tourist area of Lake Toba Parapat, Sipangan Bolon District, Simalungun Regency. The hypothesis testing used the Smart Pls program ver. 3.2.1. As a result, there is an average variable score of tangible local wisdom values that have an unfavorable category (score score below 4), namely tourism indicators of infrastructure conditions, cultural heritage indicators of mythical conditions, and lake / water state tourism. The intangible local wisdom has an unfavorable category (score score below 4) which is an indicator of honesty, full of tenderness, indicators of concern, deliberation, and indicators of courtesyThe R-Square value of 0.597 indicates a strong model. The number 0.597 means that the Local Economic Development (LED) which is able to be explained by the local wisdom variable is only 59.70%. Local wisdom have a positive relationship and significant influence on Local Economic Development (LED)